Brucella suis Seroprevalence and Associated Risk Factors in Dogs in Eastern Australia, 2016 to 2019 - Kneipp, Catherine C.; Sawford, Kate; Wingett, Kate; Malik, Richard; Stevenson, Mark A.; Mor, Siobhan M.; Wiethoelter, Anke K. (Frontiers in Veterinary Science, 2021)
Brucella suis is a zoonotic disease of feral pigs that also affects pig hunting dogs, pig hunters and veterinary staff. In recent years the incidence of disease in the eastern Australian states of New South Wales (NSW) and Queensland (QLD) has increased. A cross-sectional study was conducted to investigate the seroprevalence, geographical extent and risk factors for B. suis in dogs at-risk of contracting the disease. Eligible dogs were those that were known to hunt or consume feral pig meat. Dogs were enrolled through private veterinary clinics and/or directly by District Veterinarians in six regions of NSW and QLD. Blood was collected by venepuncture and tested for B. suis antibodies using the Rose Bengal Test (RBT) followed by a Complement Fixation Test (CFT) if they returned a positive RBT. Owners were invited to complete a questionnaire on the dogs’ signalment, husbandry including hunting practices and locations, and any clinical signs referable to brucellosis. Of the 317 dogs included in the prevalence survey, 21 were seropositive for B. suis, corresponding with a survey-adjusted true seroprevalence of 9.3% (95% CI 0.44 to 18). True seroprevalence varied from 0-24% across eastern Australia, with highest prevalence observed in central west NSW and southern Queensland. Adjusted for other factors, dogs that shared a household with other seropositive dogs and those that travelled away from their home regions to hunt were more likely to be seropositive. Clinical signs at presentation were not predictive of serostatus, with sero-positive and -negative dogs equally likely to present with signs consistent with brucellosis. The results obtained from this study indicate that B. suis exposure is relatively common in dogs that have contact with feral pigs, with one in 10 testing seropositive. Further studies are needed to understand the progression and risk of transmission from seropositive dogs.